A genome-wide association study of facial morphology identifies novel genetic loci in Han Chinese. (20th March 2021) - Huang, Yin; Li, Dan; Qiao, Lu; Liu, Yu; Peng, Qianqian; Wu, Sijie; Zhang, Manfei; Yang, Yajun; Tan, Jingze; Xu, Shuhua; Jin, Li; Wang, Sijia; et al.
Abstract: The human face is a heritable surface with many complex sensory organs. In recent years, many genetic loci associated with facial features have been reported in different populations, yet there is a lack of studies on the Han Chinese population. Here, we report a genome-wide association study of 3D normal human faces of 2, 659 Han Chinese with autosegment phenotypes of facial morphology. We identify single-nucleotide polymorphisms (SNPs) encompassing four genomic regions showing significant associations with different facial regions, including SNPs in DENND1B associated with the chin, SNPs among PISRT1 associated with eyes, SNPs between DCHS2 and SFRP2 associated with the nose, and SNPs in VPS13B associated with the nose. We replicate 24 SNPs from previously reported genetic loci in different populations, whose candidate genes are DCHS2, SUPT3H, HOXD1, SOX9, PAX3, and EDAR . These results provide a more comprehensive understanding of the genetic basis of variation in human facial morphology.